Integrated marketing communication of Batik Jambi Berkah to sustain the new normal era - Nurizal, Hendri; Wahyudin, Uud; Rahmat, Agus (Manajemen Komunikasi, 2023)
The combination of good strategies and techniques of IMC elements can make businesses survive during a pandemic and even thrive in the new normal era. That has successfully passed the pandemic and survived the new normal era by applying a digitalized integrated marketing communication without abandoning the traditional market. This research aims to describe the integrated marketing communication management of Batik Jambi Berkah as a way to survive in the new normal era. This research uses a descriptive qualitative approach and data analysis using the model of Miles and Huberman, data reduction, data presentation, and drawing conclusions. The concept used in this study is integrated marketing communication by Belch (2021). The results of this study reveal that the integrated marketing communication approach carried out consistently by Batik Jambi Berkah includes the planning, implementation and evaluation stages, which made it successfully pass through the pandemic. Entering the new normal era, Batik Jambi Berkah are participating in events and becoming sponsors to build a brand image and interact directly with consumers and potential customers. This study concludes that from time to time, IMC elements have an important role in communications, especially marketing. By adapting and developing elements of IMC, companies can improve communication effectiveness, strengthen brand images, and achieve maximum results in product marketing. The implications of this research are expected to be a reference for further research and an example for business actors, especially MSMEs, in managing IMC elements.